Looking for new treatments of Infantile Colic - Savino, Francesco (BioMed Central, 2014)
Infantile colic is a common disturbance occurring in the first three months of life. It is a benign condition and one of the main causes of pediatric consultation in the early part of life because of its great impact on family life. Some pediatricians are prone to undervalue this issue mainly because of the lack of evidence based medicine guidelines. Up to now, there is no consensus concerning management and treatment. Literature reports growing evidence about the effectiveness of dietary, pharmacological, complementary and behavioral therapies as options for the management of infantile colic. Dietary approach, usually based on the avoidance of cow’s milk proteins in breast-feeding mothers and bottle-fed infants, more recently has seen the rise of new special formulas, such as partially hydrolyzed proteins and low lactose added with prebiotics or probiotics: their efficacy needs to be further documented. Investigated pharmacological agents are Simethicone and Cimetropium Bromide: the first is able to reduce bloating while the second could reduce fussing crying, but it has been tested only for severe infantile colic. No other pain relieving agents have been proposed until now, but some clinical trials are ongoing for new drugs. There is limited evidence supporting the use of complementary and alternative treatments (herbal supplements, manipulative approach and acupuncture) or behavioral interventions. Recent studies have focused the role of microbiota in the pathogenesis of this disturb and so new treatments, such as probiotics, have been proposed, but only few strains have been tested. Further investigations are needed in order to provide evidence-based guidelines.